The Motif of the Holy Fool and Representations of Intellectual Disability: An Attempt at a Cross-Sectional Overview - Miszczuk, Magdalena (Representations of Disability in Cultural Spaces, 2026)
The article focuses on showing the similarities between the leading romantic characters and the Fool of Christ figure. A Holly Fool is a type of saint in Orthodox culture. It consists of extreme asceticism and renunciation of social life, as well as the deliberate feigning of “stupidity.” For the romantics, this motif has become a cause for ennoblement in the culture of all kinds of disorders and mental illness.